LOW COST AUTOMATIC SUN PATH TRACKING SYSTEM (Journal of Engineering, 2011)
Solar tracking systems used are to increase the efficiency of the solar cells have attracted the attention ofresearchers recently due to the fact that the attention has been directed to the renewable energy sources. Solar tracking systems are of two types, Maximum Power Point Tracking (MPPT) and sun path tracking. Both types are studied briefly in this paper and a simple low cost sun path tracking system is designed using simple commercially available component. Measurements have been made for comparison between fixed and tracking system. The results have shown that the tracking system is effective in the sense of relatively high output power increase and low cost.